A surgical view on the treatment of Madelung's disease. Issue 5 (5th August 2015) - Sharma, N.; Hunter‐Smith, D. J.; Rizzitelli, A.; Rozen, W. M.
Summary: Benign symmetrical lipomatosis (Madelung's disease) is a rare condition of unclear aetiology characterized by numerous, unencapsulated lipomatous deposits. The only effective treatment is by surgical intervention; however, there is no consensus in the optimal approach. We present the case of a patient who required staged, multi‐modality treatment to achieve disease quiescence. The case highlights the usefulness of magnetic resonance imaging as a tool for assessment as well as preoperative planning.